Comparative performance of Kato–Katz, POC-CCA and real-time PCR in detecting Schistosoma mansoni infection at different endemicity settings in northwest Ethiopia: a cross-sectional study - Getaneh Alemu; Endalkachew Nibret; Abaineh Munshea; Melaku Anegagrie; María Flores-Chávez; Tadesse Hailu; Arancha Amor (Tropical Medicine and Health)
Abstract Background Effective detection of Schistosoma mansoni is crucial for the control and management of the infection. This study aimed to evaluate the field performance of three diagnostic methods—point-of-care circulating cathodic antigen (POC-CCA) assay, Kato–Katz (KK) technique, and real-time polymerase chain reaction (RT-PCR)—for detecting S. mansoni infection in different transmission settings across northwest Ethiopia. Methods From February to June 2023, a cross-sectional study was conducted in the Amhara Regional State of Ethiopia, involving 1192 randomly selected participants. Stool samples were analyzed using the KK technique and RT-PCR, while urine samples were tested using the POC-CCA cassette. The performance of POC-CCA and RT-PCR was evaluated against a KK reference standard across varying transmission areas. In addition, diagnostic accuracy for all three methods was assessed using latent class analysis (LCA) with Mplus software. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and kappa statistics were calculated using the Simple Interactive Statistical Analysis (SISA) online tool. Results The KK method showed the lowest prevalence (33.4%) and demonstrated reduced sensitivity, particularly in low (54.6%) and moderate (67.0%) transmission areas, though it performed better (88.6%) in high-endemic settings compared to LCA reference. In contrast, the POC-CCA test showed higher prevalence (53.5%) and consistently high sensitivity (93.4–100%) across transmission settings, although its specificity declined in low (86.0%) and moderate (78.9%) endemic areas against LCA. Compared to the KK gold standard, POC-CCA had high sensitivity (93.5%) and NPV (95.3%) but lower specificity (62.5%) and moderate agreement (kappa = 0.52). RT-PCR exhibited strong diagnostic performance, with high sensitivity against both KK (93.5%) and LCA (97.2%) but declining specificity as endemicity increased (84.2% in low, 79.4% in moderate and 28.0% in high-endemic areas), and showed substantial agreement with LCA (kappa = 0.75). Conclusions The KK demonstrates low sensitivity, particularly in low-transmission settings. Both the POC-CCA test and RT-PCR show good performance for detecting S. mansoni infection. However, due to its complexity and resource requirements, RT-PCR is not feasible for routine field use. Therefore, we recommend the adoption of the POC-CCA test in Ethiopia’s SCH control and elimination programs.